The effects of a firefighting simulation on the vascular and autonomic functions and cognitive performance: a randomized crossover study - Teixeira, Iara G.; Verzola, Marcio R.; Filipini, Richard E.; Speretta, Guilherme F. (Frontiers in Physiology, 2023)
Introduction: During firefighting, physical and cognitive demands increase. However, the stress inherent to these events can decrease cognitive performance and increase the risk of cardiovascular events in firefighters. Thus, this crossover study aimed to evaluate the effects of a firefighting Simulation on cognitive performance and vascular and autonomic functions in military firefighters. Methods: Sixteen firefighters (37.8±5.6 years) underwent anthropometry, mental health status, and sleep quality assessments. They randomly performed two interventions, Simulation (Firefighting tasks; 10.0±1.1 min) and Control (rest for 10 min), on different days. After both interventions, cognitive performance was assessed using the Stroop Test, Paced Auditory Serial Addition Test, and Trail Making Test. Then, the vascular function was assessed using ultrasonography through the carotid artery reactivity to the cold pressor test. The arterial pressure, heart rate, and cardiac intervals were recorded before interventions. The cardiac intervals were also measured during the cold pressor test. Student's t-test and Wilcoxon were used for comparisons between Control and Simulation and the analysis of variance for repeated measures was used for comparison over time during the cold pressor test. A significance level of P<0.05 was adopted. Results: Although the mean and maximum heart rate were higher before the Simulation (P<0.0001), all the heart rate variability parameters (P>0.05) and mean arterial pressure (P>0.3795) were similar before the interventions. After Simulation, the cognitive performance was similar to Control (P>0.05), except for the improvement in Stroop Test part B (P<0.0001). After Simulation, carotid artery reactivity was attenuated (P<0.0010). During the cold pressure test, the high-frequency band of the heart rate variability was lower after the Simulation (P<0.0104). Discussion: Although firefighting Simulation did not substantially change cognitive performance, the lower carotid artery reactivity and parasympathetic modulation to the heart during the cold pressure test may contribute to greater vulnerability to cardiovascular events in firefighters on duty. Clinical Trial Registration: Brazilian Registry of Clinical Trials (ReBEC; no. RBR-24db7p7).